Recent Progress in Enantioselective Alkylation of Metal Enolates - Li, Hui; Yin, Liang (Synthesis, 2025)
The enantioselective alkylation of metal enolates serves as a particularly versatile tool for the construction of α-chiral carbonyls, which are ubiquitous motifs in organic chemistry. Both stoichiometric asymmetric induction reactions and catalytic asymmetric methods contribute to this field, with the latter more step- and atom-economic. In this short review, we summarize the recent achievements in this field. Both chiral lithium amide-directed manner (stoichiometric methods) and transition metal-catalyzed manner (catalytic methods) are covered separately. Moreover, both stabilized enolates and unstabilized enolates are employed as active nucleophiles, and both activated and nonactivated alkyl electrophiles serve as valid alkylation reagents. The mechanisms, especially the origin of the stereoselectivity, and the potential applications of some representative methodologies are also included.
Keywords: Enantioselective alkylation; Metal enolates; Stoichiometric method; Trace auxiliary; Transition-metal catalysis; Activated alkyl electrophiles; Nonactivated alkyl electrophiles